(α − ψ) Meir–Keeler Contractions in Bipolar Metric Spaces - Manoj Kumar; Pankaj Kumar; Rajagopalan Ramaswamy; Ola A. Ashour Abdelnaby; Amr Elsonbaty; Stojan Radenović (Mathematics, 2023)
In this paper, we introduce the new notion of contravariant <semantics>(α−ψ)</semantics> Meir–Keeler contractive mappings by defining <semantics>α</semantics>-orbital admissible mappings and covariant Meir–Keeler contraction in bipolar metric spaces. We prove fixed point theorems for these contractions and also provide some corollaries of main results. An example is also be given in support of our main result. In the end, we also solve an integral equation using our result.